Eksistensi Akuntansi Sumber Daya Manusia Sebagai Aset - Satria Darma (JAS (Jurnal Akuntansi Syariah), 2020)
This research aims to analyze the recognition of the existence of human resource as assets in the financial statements and the various obstacles encountered in the application of human resources accounting. This research uses a descriptive analysis in analyzing secondary data related to these issues. Therefore, the need for encouragement through empirical research to create uniformity in the measurement of human value and also efforts to revisit the definition of assets, so that the human resource could be recognized as asset and then is also recognized as General Accepted Accounting Principle.